Truth and Truth-telling in Dietrich Bonhoeffer: Reconsidered after 3.11 and “Fukushima” - Shimada, Yuki (Theology today, 2014)
This article investigates Bonhoeffer's understanding of truth and truth-telling as displayed in his essay “What Does It Mean to Tell the Truth?” as well as in his academic works, Sanctorum Communio and Act and Being. The article indicates that he understood truth and truth-telling essentially in connection with the relation to the other person as a God-given reality. In addition, the article explicates that this understanding is present, not only in the article, which he wrote in the midst of his struggle with the truth and untruth of the Nazis, but also in the very beginning of his theological life, determining his systematic theological thinking. The article then explores Bonhoeffer's understanding of truth and truth-telling in the context of post-Fukushima Japan. Since the accident at the Fukushima Daiichi Nuclear Power Plant following the earthquake in March 2011, there have been numerous truthful and untruthful discourses as well as different interpretations of facts concerning radioactivity and radioactive contamination. How can we approach the situation if we intend our discourse to be truthful? Bonhoeffer's insight to consider truth and truth-telling in relation to the other person appears to be rich in suggestions for the current situation in Japan.